2021
DOI: 10.1021/acsami.1c07863
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Siloxane-Terminated Side Chains in Small Molecular Donors for All-Small-Molecule Organic Solar Cells: Modulated Molecular Orientation and Enhanced Efficiency

Abstract: In this work, three small molecular donors (SMDs) S35, S35–1Si, and S35–2Si, with 3,5-difluorophenyl-substituted benzodithiophene as the central 2-dimensional unit to combine different numbers of siloxane-terminated side chain, were synthesized for all-small-molecule organic solar cells (ASM-OSCs). The three SMDs showed comparable film absorption peaks at 570 nm and optical band gaps of 1.8 eV. Relative to S35 and S35–1Si with symmetric alkyl side chains and asymmetric side chains on the central unit, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…Chen's team designed and synthesized small molecules S35, S35-1Si and S35-2Si by substituting the alkylthiophene side groups of BTR with 3,5-diuorophenyl units with different numbers of siloxane-terminated side chains. 78 The introduction of siloxane-terminated side chain exhibits ignorable inuence upon the optical bandgap and absorption coef-cients. And all three small molecules deliver edge-on dominated orientations in neat lms.…”
Section: Benzodithiophene-central Core Based Small Molecular Donorsmentioning
confidence: 99%
“…Chen's team designed and synthesized small molecules S35, S35-1Si and S35-2Si by substituting the alkylthiophene side groups of BTR with 3,5-diuorophenyl units with different numbers of siloxane-terminated side chains. 78 The introduction of siloxane-terminated side chain exhibits ignorable inuence upon the optical bandgap and absorption coef-cients. And all three small molecules deliver edge-on dominated orientations in neat lms.…”
Section: Benzodithiophene-central Core Based Small Molecular Donorsmentioning
confidence: 99%
“…Importantly, it was clearly observed that the σ of composite fibers at 240°C and 250°C were higher than that of the neat PMMA. This behavior was attributed to the improvement on the entanglement of the molecular chain, 41,42 resulting from the construction of orientation structure with “head‐to‐tail” (Figure 2). Afterwards, the mechanical comparison corresponded to the rheological performance of microfiber orientation could confirm that elongation at break were greatly attributed to microfiber orientation.…”
Section: Resultsmentioning
confidence: 99%
“…The locations of the (100) peaks on the IP direction for 35Si and 23Si and (100) peaks on the OOP direction of 35Si are slightly decreased compared with the alkyl side chain substituted polymers, which is a common variation for polymer donors with a siloxaneterminated side chain. 38,42…”
Section: Molecular Packing Of Neat Polymer Filmsmentioning
confidence: 99%